The anthropological analysis of skeletons from Puščavaabove Stari trg near Slovenj Gradec - Leben-Seljak, Petra (Arheološki vestnik, 2004)
The article presents the results of anthropological analysisof 53 skeletons from the cemetery at Puščava above Stari trgnear Slovenj Gradec (5th -9th centuries), the intent of whichwas to establish whether or not a change in the populationoccurred at Puščava during that period (the previously presentinhabitants from the late Roman period opposed to the newlyarrived early Slavs). The results allow for both possibilities.There was no difference between the skeletons from the lateRoman period and the early medieval period in terms of themorphological characteristics of neurocrania, stature, and thedegree of dental caries. The series as a unit is quite homoge-nous and in terms of the mentioned characteristics occupiesa median position between comparative series from late antiq-uity at Pristava I and Vrajk on the one hand, and from theearly Slavic period at Pristava II and Turnišče on the other.